EFFECT OF GENOTYPE AND AGRO-ECOLOGICAL CONDITIONS ON FRUIT QUALITY OF OBLAČINSKA SOUR CHERRY - Nikolić, Dragan; Vuković Vimić, Ana; Vujadinovic Mandić, Mirjam (ACADEMIC REVIEW, 2021)
During 2020 and 2021, the most important physicochemical fruit traits of four Oblačinska sour cherry clones selected from production orchards at the Grocka locality were studied. Significant effect of genotype was determined for all physical and chemical fruit traits, except for the soluble solid content. The influence of year was significant for fruit weight, fruit width, fruit thickness, as well as stone weight, stone dimensions and total sugar content. The largest fruit weight had clone OK1 (3.63 g), and the smallest clone OK4 (3.01 g). All tested clones had a high soluble solid content that varied from 19.25% (clone OK4) to 20.05% (clone OK1). The total acids content ranged from 1.08% (clone OK1) to 1.16% (clone OK3). In terms of the examined traits, clones OK1 and OK3 stood out, which are interesting for introduction into production and further breeding work.